2017
DOI: 10.24036/ld.v11i1.7938
|View full text |Cite
|
Sign up to set email alerts
|

An Interlanguage Error Analysis: A Formative Evaluation for Freshmen

Abstract: This paper aims at finding the interlanguage errors made by the freshmen of English Department of Universitas Negeri Padang. This research needs to be conducted since the result can become a formative evaluation for lecturers in teaching English for the freshmen. The method used in this reserach is a qualitative-descriptive method, supported by simple quantitative calculation. The data were taken from students’ mid term examination. The mid term examination included multiple choice, cloze procedure and composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…In another study carried out by Al-husban on 33 first year undergraduate students in 2017, it was identified that there were 103 omission errors (31,3%), 82 addition errors (24,9%), 76 misformation errors (23,2%) and 68 misordering errors (20,6%) in student works. Finally, Tiarina (2017) observed in the study on university first year students that students made 27 omission errors (47%), 16 misformation errors (28%), 12 addition errors (21%) and only 2 misordering errors (4%). These studies indicate that misordering is the least frequent error category among students.…”
Section: Discussion Conclusion and Recommendations Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In another study carried out by Al-husban on 33 first year undergraduate students in 2017, it was identified that there were 103 omission errors (31,3%), 82 addition errors (24,9%), 76 misformation errors (23,2%) and 68 misordering errors (20,6%) in student works. Finally, Tiarina (2017) observed in the study on university first year students that students made 27 omission errors (47%), 16 misformation errors (28%), 12 addition errors (21%) and only 2 misordering errors (4%). These studies indicate that misordering is the least frequent error category among students.…”
Section: Discussion Conclusion and Recommendations Discussionmentioning
confidence: 87%
“…Lastly, they are important for the learners themselves as they make use of their error to learn the correct form of the language. James (1998; as cited in Tiarina, 2017), on the other hand, explained that errors were important in two different dimensions. Analysis of errors explains teachers what to do in teaching the foreign language and informs researchers how the process of learning progresses.…”
Section: The Importance Of Errorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the errors produced by EFL learners due to the processing of learning or acquiring a target language (Al-Khresheh, 2015). Tiarina (2017) studied interlanguage performed by students of the English literature study program. The subjects of the study were 20 English Literature students.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, code-mixing also facilitates the students in understanding new terms of the target language like grammar and new vocabulary. Tiarina (2017) investigated the interlanguage error produced by freshmen. The participants were freshmen who took an intensive course.…”
Section: Introductionmentioning
confidence: 99%